Legal protections for children in refugee and migrant crises in central and Eastern Europe - Garayová, Lilla (Frontiers in Political Science, 2025)
Child refugees and migrant children in Central and Eastern Europe are among the most vulnerable populations in humanitarian crises, underscoring the urgent need for legal protections grounded in the best interests of the child principle. This study provides an in-depth legal analysis of international, regional, and national frameworks, focusing on Central and Eastern Europe-particularly Slovakia, Czechia, Hungary, and Poland-to evaluate how well these laws uphold children's rights in practice, especially in the areas of family reunification and education access. Drawing on case law from European and national courts, empirical data from recent crises (such as the Ukrainian refugee influx), and policy reports, the analysis highlights how key legal principles are applied, including the best interests of the child, the right to family reunification, access to education, and special protections for unaccompanied children. The findings reveal both successes and gaps: strong legal standards exist and have been effectively mobilized in certain contexts (for example, during the Ukrainian refugee influx under the European Union's Temporary Protection regime), yet consistent implementation and enforcement remain a challenge across the region. Finally, the study offers policy recommendations aimed at strengthening legal frameworks and practices to ensure that the rights of children in migration crises are fully protected.